Early intervention of acute liver injury related to venlafaxine: A case report. Issue 49 (10th December 2021) - Fang, Lin; Wang, Shushan; Cao, Leiming; Yao, Kun
Abstract: Rationale: Drug-induced liver injury (DILI) is the leading cause of acute liver injury (ALI), market withdrawal of a drug, and rejection of applications for marketing licenses. The incidence of DILI is very low, with a value between 1 and 19 per 100, 000 patient years. All antidepressants may induce DILI even at low therapeutic doses. In this report, we present a case of ALI after venlafaxine administration. Patient concerns: A 27-year-old Chinese Han woman was admitted for depression. Several serum liver function indices in this patient were abnormal after antidepressant treatment. The Roussel Uclaf Causality Assessment Method (RUCAM) causality assessment score was 8, and the R value was 31.18. Diagnoses: The patient was diagnosed with hepatocellular ALI, which was derived from venlafaxine-related adverse events. Interventions: First, all medications were stopped to block the progression of DILI. Then, a hepatoprotective strategy and proper psychological treatment were performed to recover the impaired hepatic function. Outcomes: Liver function was fully recovered as indicated by liver function indices and ultrasound imaging. Lessons: The possibility of DILI should not be overlooked during the long-term use of antipsychotic drugs. In response, regular liver function monitoring should be performed in a timely manner to avoid missing diagnoses and delayed treatment. Furthermore, the necessary medical treatment needs to be conducted after the occurrence of ALI.